An evaluation of treatment integrity in a randomized trial of behavioural therapy for low mood in stroke patients with aphasia. (December 2013) - Thomas, Shirley A; Russell, Claire; Seed, Ruth; Worthington, Esme; Walker, Marion F; Macniven, Jamie A; Lincoln, Nadina B
Objective: To assess the treatment integrity of behavioural therapy for low mood in stroke patients with aphasia. Design: Participants were recruited to a multicentre randomized controlled trial (Communication and Low Mood; CALM trial) comparing behavioural therapy with a usual care control group. Subjects: Of the 51 participants randomly allocated to receive behavioural therapy, 44 participants completed treatment. Methods: Participants were assessed on measures of disability, language and mood. The number and length of therapy sessions, and therapist was recorded. Allocation of time to therapy components was compared across three phases of therapy. Associations between levels of disability, aphasia, mood and the therapy patients received were determined. Therapy content was compared between centres and at the beginning and end of the trial. Results: The mean number of therapy sessions was 9.1 (range 3–18, SD 2.6) and the mean duration of sessions was 58 minutes (range 30–89 minutes, SD 10.7). Allocation of time to each therapy component significantly differed across the three phases of therapy ( P < 0.05). There were no significant associations ( P > 0.05) between the length and number of sessions and patients' aphasia, mood or disability, suggesting similar levels of therapy were provided regardless of patients' characteristics. The content of therapy showed some differences between centres ( P < 0.01) and there was programme drift in some components of therapy. Conclusions: The results support the ability of the therapists to deliver behavioural therapy according to the treatment manual. However there were differences between centres and over time in some components of therapy.